After Apollo : cultural legacies of the race to the moon - Bennington, J. Bret, 1963-; Hill, Rodney F. (University of Florida Press, 2023)
"This book explores how NASA's space program impacted American society and culture during and after the race to the Moon, looking back at the 1969 Apollo 11 Moon landing from the perspective of the present day"--